The Rise of the Middle Class and Economic Growth in ASEAN - Brueckner, Markus; Dabla-Norris, Era; Gradstein, Mark; Lederman, Daniel (World Bank, Washington, DC, 2017)
This paper presents estimates of the relationship between the share of income accruing to the middle class and gross domestic product per capita of economies from the Association of Southeast Asian Nations. The increase in gross domestic product per capita that these economies experienced during 1970–2010 significantly contributed to a higher share of income accruing to the middle class. The impact of the rise of the middle class on economic growth depends on the countries' initial level of gross domestic product per capita. In the majority of these countries, a rise of the middle class that is unrelated to gross domestic product per capita growth would have had a significant negative effect on economic growth, based on the values of the countries' gross domestic product per capita in 1970. In contrast, for recent values of gross domestic product per capita, a rise of the middle class would positively contribute to growth in gross domestic product per capita. The paper shows that human capital accumulation is an important channel through which a rise of the middle class affects economic growth.